Doświadczając historii: melancholia przeszłości w kulturach peryferyjnych na przykładzie Polski i Portugalii - Partyka, Joanna (Tematy i Konteksty, 2019)
In this paper I combine several different notions from broadly conceived humanities and two histories: of Poland and of Portugal at the turn of the 16th and 17th centuries. I comprehend here the experiencing of history as a way of treating one’s own, national past. The metaphor of experiencing history is related to the question of what the historical circumstances and situations are, what the purpose is and what history is referred to by the elites who are instrumental in shaping national identity. Melancholy of the past is already a partial answer-thesis to the question: In what way? The notion of peripheral cultures seems to be useful when we attempt to answer the question: in what situations and for what purpose we (the Portuguese and the Poles) referred, but also still continue to refer, to the past/history. Some considerations on the experience of history will have the following two Unions in the background: the Iberian Union (1580) and the Union of Lublin (1569).